Surround by Sound: A Review of Spatial Audio Recording and Reproduction - Wen Zhang; Parasanga N. Samarasinghe; Hanchi Chen; Thushara D. Abhayapala (Applied Sciences, 2017)
In this article, a systematic overview of various recording and reproduction techniques for spatial audio is presented. While binaural recording and rendering is designed to resemble the human two-ear auditory system and reproduce sounds specifically for a listener’s two ears, soundfield recording and reproduction using a large number of microphones and loudspeakers replicate an acoustic scene within a region. These two fundamentally different types of techniques are discussed in the paper. A recent popular area, multi-zone reproduction, is also briefly reviewed in the paper. The paper is concluded with a discussion of the current state of the field and open problems.